Pendampingan Wisata Petik Jeruk sebagai Inisiasi Agroeduwisata di Kebun Inovasi Politeknik Negeri Jember: Assistance in Citrus Picking Tourism as an Agroedu-Tourism Initiative at the Innovation Farm of the State Polytechnic of Jember - Napitupulu, Tia Sofiani; Nadhirah, Aulia; Sumarlina, Sumarlina; Marseva, Amalia Dwi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The Innovation Farm at the State Polytechnic of Jember has initiated a citrus-picking tourism program to develop agroedu-tourism based on the Teaching Factory (TeFa) concept. Assistance activities were carried out to help managers understand the concept of educational tourism, manage visitor experiences, and develop Standard Operating Procedures (SOPs). The implementation included planning, operational assistance, SOP formulation, and evaluation. The results showed improvements in managerial capacity, particularly in knowledge, skills, and management aspects. After the assistance, the citrus-picking tourism became more structured, with SOPs being implemented and supporting facilities better prepared. This initiative opens opportunities for managers to develop tourism potential and serves as an initial step toward a more mature and sustainable agroedu-tourism model in the future.